Modern Endoscopic Imaging in Diagnosis and Surveillance of Inflammatory Bowel Disease Patients - Gheorghe Hundorfean; Stephen P. Pereira; John G. Karstensen; Peter Vilmann; Adrian Saftoiu (Gastroenterology Research and Practice)
Endoscopy remains the most important diagnostic and monitoring modality in the management of inflammatory bowel disease. Advances in imaging have progressively added new tools into the armamentarium of endoscopists with the goal of more accurate, sensitive, and accessible visual diagnoses for the benefit of patients with gastrointestinal diseases. Here, we review the relevant literature regarding commonly used endoscopic techniques (dye-based and digital chromoendoscopy, high-definition endoscopy, capsule endoscopy, and endosonography), as well as advanced and experimental technologies (full-spectrum endoscopy, endocytoscopy, autofluorescence, laser endoscopy, and endomicroscopy, including molecular imaging), applicable to inflammatory bowel diseases and emerging for implementation into everyday practice. Additionally, we discuss future directions and techniques as candidates for a superior inflammation imaging in the diagnosis and prediction of therapeutic response.